2022
DOI: 10.1002/pon.6058
|View full text |Cite
|
Sign up to set email alerts
|

Communication about diagnosis and prognosis—A population‐based survey among bereaved parents in pediatric oncology

Abstract: Introduction:When a child is diagnosed with cancer, the whole family is affected, and parents struggle to grasp challenging information regarding diagnosis and prognosis. Most parents and children want honest communication and openness, yet this remains a complex and challenging task for healthcare professionals.Objectives: To describe bereaved mothers' and fathers' reports of communication of their child's cancer diagnosis and when the illness became incurable.Methods: Data from a Swedish population-based sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Regarding trust, from the six (35.29%) QD studies [ 11 , 16 , 20 , 24 , 27 , 30 ], it was observed that most parents trusted their physicians/hospital/treatment highly or even completely (n = 1139, 73.01%). However, about a fifth of caretakers (n = 326, 20.90%) declared low levels of trust.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Regarding trust, from the six (35.29%) QD studies [ 11 , 16 , 20 , 24 , 27 , 30 ], it was observed that most parents trusted their physicians/hospital/treatment highly or even completely (n = 1139, 73.01%). However, about a fifth of caretakers (n = 326, 20.90%) declared low levels of trust.…”
Section: Resultsmentioning
confidence: 99%
“…However, about a fifth of caretakers (n = 326, 20.90%) declared low levels of trust. Regarding parental distress, from the four (23.53%) QD studies [ 11 , 12 , 20 , 24 ], it was observed that most parents (n = 365, 46.68%) claimed moderate levels of distress or a need for psychosocial support. However, about a third (n = 269, 34.40%) signaled high levels.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations